URGENSI METODE OMNIBUS LAW DALAM PEMBENTUKAN PERUNDANG-UNDANGAN DI INDONESIA DIKAITKAN DENGAN TUJUAN WALFARE STATE - Geofani Milthree Saragih (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2022)
Some time ago, there was a debate in the world of constitutional law, especially in legislation. This is because in early 2020, the use of the Ombibus Law method was realized in the formation of several bills that were included in the priority prolegnas. In particular, the use of the Ombibus Law method is part of the implementation of the government's political agenda in improving several legal problems in Indonesia, especially in the world of employment. Then, one of the arguments used is to realize people's welfare through expanding employment opportunities. This can be seen from the enactment of Law Number 11 of 2020 concerning Job Creation where the formation of the law uses the Ombibus Law method which has never been used in Indonesia, moreover, this method is generally used in countries that adhere to the common law legal system. . One of the problems that arise from this situation is the submission of a judicial review of Law Number 11 of 2020 concerning Job Creation. The tests carried out on the law were a material test and a formal test, in which the application for a formal review contained in the application to the Constitutional Court included an objection to the use of the Ombibus Law method which does not have a clear legal basis in positive law in Indonesia. The research method used in this research is normative research with analytical descriptive nature. This study aims to find out how the urgency of the Omnibus Law method in the formation of laws in Indonesia is related to the goal of the welfare state. The results of this study will answer how the urgency of using the Omnibus Law method in Indonesia is and what is its relation to the goal of the welfare state